Causal relationship between obesity and anorectal abscess: a Mendelian randomization study - Zeng, XiaoYu; Wang, HanYu; Deng, Yang; Deng, ZhiYu; Bi, Wei; Fu, Hao (Frontiers in Medicine, 2024)
Background: Observational studies have indicated that obesity is a risk factor for anorectal abscess (ARB). However, it remains unclear whether a causal genetic relationship exists between obesity and ARB.Methods: Univariate and multivariate Mendelian randomization (MR) were conducted using data from a large, published genome-wide association study (GWAS) of European ancestry to infer a causal relationship between obesity and ARB. Inverse variance weighted (IVW) analysis served as the primary analysis method, with results reported as odds ratios (OR).Results: MR analysis revealed that body mass index(BMI) positively affects ARB (OR 1.974, 95% confidence interval (CI) 1.548-2.519, P = 4.34E-08). The weighted median method (OR=1.879, 95% CI 1.248-2.829, P = 0.002) and Bayesian model averaging (BMA) (OR=1.88, 95% CI 1.477-2.392, P = 2.85E-07) also demonstrated consistent results. Subsequently, the impact of several obesity-related characteristics on ARB was assessed. Body fat percentage (BF), whole body fat mass (FM), waist circumference (WC), and hip circumference (HC) were found to be causally associated with an increased risk of ARB. However, these associations vanished after adjusting for BMI effects.The study confirms a positive causal effect of obesity on ARB, highlighting that reasonable weight control is an important strategy to reduce the incidence of ARB.